2006
DOI: 10.1002/pca.921
|View full text |Cite
|
Sign up to set email alerts
|

Application of principal components analysis to 1H‐NMR data obtained from propolis samples of different geographical origin

Abstract: Propolis is a widely used natural remedy and a range of biological activities have been attributed to it. The chemical composition of propolis is highly variable and its quality is often controlled on the basis of one or two marker compounds. In order to progress towards a method for the quality control of this complex material, HPLC and 1H-NMR approaches as methods of quality control have been compared. HPLC analyses of 43 samples of propolis were carried out and six marker compounds were quantified in each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 29 publications
0
29
0
2
Order By: Relevance
“…[11] Moreover, it was observed that antioxidant properties mapped quite well according to geographical origin. [12]…”
Section: Chemical Compositions Of Propolismentioning
confidence: 99%
“…[11] Moreover, it was observed that antioxidant properties mapped quite well according to geographical origin. [12]…”
Section: Chemical Compositions Of Propolismentioning
confidence: 99%
“…Propolis is a resinous hive product produced by honeybees from various plant sources. It is used in the hive to seal holes, smooth out the internal walls, and protect the entrance against intruders 1. The use of propolis as alternative food and medicine in many countries has increased in the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…, 2002). In general, there have been several applications of NMR spectroscopy to propolis analysis (Watson et al. , 2006; Cuesta‐Rubio et al.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of much higher magnetic fields and the greater sensitivity that they bring have stimulated interest in one-dimensional (1D) and bidimensional (2D) NMR spectroscopy as a routine method for the analysis of complex mixtures (Fan, 1996;Charlton et al, 2002). In general, there have been several applications of NMR spectroscopy to propolis analysis (Watson et al, 2006;Cuesta-Rubio et al, 2007;Kumazawa et al, 2007); however the 1D and 2D NMR, to our knowledge, have never been previously applied to propolis in effort to classify samples according to the method of harvest.…”
Section: Introductionmentioning
confidence: 99%